Mass concentration measurements of autumn bioaerosol using low-cost sensors in a mature temperate woodland free-air carbon dioxide enrichment (FACE) experiment: investigating the role of meteorology and carbon dioxide levels - A. B. Baird; A. B. Baird; E. J. Bannister; E. J. Bannister; A. R. MacKenzie; A. R. MacKenzie; F. D. Pope; F. D. Pope (Biogeosciences, 2022)
Forest environments contain a wide variety of airborne biological particles (bioaerosols), including pollen, fungal spores, bacteria, viruses, plant detritus, and soil particles. Forest bioaerosol plays a number of important roles related to plant and livestock health, human disease and allergenicity, and forest and wider ecology and are thought to influence biosphere–atmosphere interactions via warm and cold cloud formation. Despite the importance of bioaerosols, there are few measurements of forest aerosol, and there is a lack of understanding of how climate change will affect forest bioaerosol in the future.